2012
DOI: 10.3748/wjg.v18.i35.4962
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic schwannoma: Imaging findings on CT, MRI and contrast-enhanced ultrasonography

Abstract: Metastases of esophageal carcinoma to the skeletal muscle are rare, but the incidence may be increasing because of better diagnosis resulting from widespread use of positron emission tomography/computed tomography (PET/CT). A cohort of 205 patients with esophageal carcinoma treated at our center who had PET/CT between 2006 and 2010 was retrospectively evaluated for the presence of skeletal muscle metastases. Four patients had skeletal muscle metastases of esophageal carcinoma, including two patients with squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…As described previously, the majority of patients were admitted with the complaint of pain or discomfort in the upper abdomen or epigastrium (5). In the present study, 8 patients were asymptomatic, whose liver tumors were found during routine examination or the follow-up when combined with other diseases.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As described previously, the majority of patients were admitted with the complaint of pain or discomfort in the upper abdomen or epigastrium (5). In the present study, 8 patients were asymptomatic, whose liver tumors were found during routine examination or the follow-up when combined with other diseases.…”
Section: Discussionmentioning
confidence: 83%
“…However, since hepatic schwannoma is such a rare finding, a definitive diagnosis by radiological methods is difficult. Liver biopsy may be useful for accurate preoperative diagnosis (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Although a schwannoma may arise from any organ that contains peripheral nerves, primary hepatic schwannomas are extremely rare. According to English medical literature, only 19 cases of hepatic schwannoma, including the presently reported case, have been documented (Table 1) [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18]. These 19 cases consisted of 9 men (47.1%) and 10 women (52.9%), with a median age of 56 years (range, 21–83 years).…”
Section: Discussionmentioning
confidence: 99%
“…These radiological findings are consistent with those of typical acoustic schwannomas or schwannomas originating in more common locations. Ota et al [14] reported that contrast enhanced US was useful in diagnosing hepatic schwannoma and it showed minute arterial flow into the tumor along the nodal septum during the vascular phase and the delayed enhancement of solid areas during the postvascular phase. Although the radiological characteristics of the present tumor were similar to those of schwannoma when considered retrospectively, a precise diagnosis of primary hepatic schwannoma is still considered to be difficult because of the extreme rarity of this tumor and its radiological similarity to a mucus-producing tumor or adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, only one study describes a rare case of hepatic schwannoma studied with CEUS [7] and only one case of leydigioma studied with both CEUS and US-elastography has been reported [8].…”
Section: Introductionmentioning
confidence: 99%